PENGARUH MODEL HYBRID LEARNING TERHADAP LEVEL KOGNITIF PADA MATA KULIAH FISIKA DASAR - Sumihar Simangunsong; Jelita Panjaitan (Lembaga Penenlitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2022)
This research is motivated by the low learning outcomes of students in basic physics subjects. This is due to the basic physics learning requires mathematical analysis in interpreting and analyzing the variables of physical quantities. The purpose of this study was to see the increase in learning outcomes as a result of applying the Hybrid learning model with a basic calculus approach. This approach is used because basic calculus can analyze the substance of basic physics through differential and integral languages. The sample of this research is students majoring in mining ISTP Medan. The research method used is a quasi-experimental one group design. To see the learning outcomes, the learning outcomes test is used and the gain test is used to improve learning outcomes. The results showed that the gain test at the first meeting was 0.5, the second meeting was 0.6 and the third meeting was 0.6 in the high category. Because there is an increase in gain in each meeting, it is concluded that there is an increase in student learning outcomes as a result of learning the Hybrid learning model with a basic calculus approach.